Evaluating responses to health-related messages about the financial costs of climate change - Vijay S. Limaye; Benjamin Toff (Elsevier, 2023)
Introduction: Science communication research has increasingly explored what factors shape public opinion around climate change policies. The public health consequences of climate change are becoming an increasingly prominent focus of research and policy, and prior research has identified the importance of health messaging for effective risk communication efforts. While prior research on communication appeals that highlight the impact of climate change on public health has shown promise, evidence around the effectiveness of such appeals remains thin, especially around health-related financial costs related to climate hazards. Materials: We explore how social media messages that describe the ramifications of climate-related health problems may influence support for climate change policies. We fielded an experiment embedded in an online survey of 2,859 English-speaking U.S. adults to understand how health-cost climate messaging may have a differential impact on distinct segments of the public. Treatment groups read a hypothetical social media post about how a failure to invest in climate change mitigation and adaptation may result in financial burdens from either damaged property or healthcare costs due to worsening climate hazards quantified at either a national or household scale. Following exposure to treatment stimuli, respondents were asked to state to what extent they perceived climate change to be a threat to the US, supported policy responses, and supported federal investments in mitigation and adaptation. Results: While all messaging conditions were associated with significantly higher perceptions that climate change poses a threat, no differences were observed when comparing across the health- versus property-related economic damage messages. Conclusion: Communication of costs on a per household basis was associated with significantly higher perceptions that climate change is a threat compared to messages that emphasized costs at a national level.